Evaluation of jute leaf as substitute of fish meal in the diet of mrigal (Cirrhinus cirrhosus) fingerlings - Rana, KMS; Biswas, P; Salam, MA (International Journal of Agricultural Research, Innovation and Technology, 2020)
The study was conducted to identify jute leaf powder as an alternate to fish meal in diets of juvenile mrigal (Cirrhinus cirrhosus) for 60 days. Tossa jute (Corchorus olitorius) leaf was selected to utilize this unexplored nutritious resource rather leaving under water for potential pollution. Three isonitrogenous test diets were prepared and applied as treatments (T) in triplicates (R). In control (T0) dietary inclusion rate of fish meal was 30%, of which 10% was substituted with jute leaf powder in T10 and in T20 replacement was 20%. Mrigal fingerlings (9.38±0.13 cm and 7.94 ±0.26 g) were stocked in nine plastic half drums (0.26 m2 each) at 10 fish per drum and fed test diets. Although, growth parameters among the treatments were statistically similar, the highest mean length gain, weight gain, SGR and production were 1.51 (±0.18) cm, 2.96 (±0.13) g, 0.53 (±0.03) %/day and 4084.00 (±50.67) kg ha-1, respectively in T10. However, significantly higher (P<0.05) survival was found in T10 (93.33%) and T20 (90.00%) compared to T0 (83.33%). Juveniles in T10 and T20 showed better tolerance to low pH stress than T0. Water quality parameters were within acceptable range in all the treatments. Moreover, carcass composition of fish was statistically similar among the treatments. Importantly, feed formulation cost was reduced by 3.7% and 20.4% in T10 and T20, respectively compared to T0. Therefore, the results signify that jute leaf powder could be a promising substitute of fishmeal in mrigal diet without hampering growth along with improved survival and low feed cost. Int. J. Agril. Res. Innov. Tech. 10(1): 117-122, June 2020